ON HARMONIOUS COLORING OF C(Hn) AND C (Gn) - G, Jothilakshmi. (Journal of Global Research in Mathematical Archives(JGRMA), 2015)
A harmonious coloring is a proper vertex coloring in which every pair of colors appears on at most one pair of adjacent vertices. In this paper harmonious coloring of C ( ) and C (Gn) are studied. Some structural properties of them are discussed. Also, their harmonious chromatic number was obtained. Keywords: Graph coloring, middle graph, helm graph, Gear graph, harmonious coloring and harmonious chromatic number. Classification number: 05C15, 05C75